2019
DOI: 10.1371/journal.ppat.1007551
|View full text |Cite
|
Sign up to set email alerts
|

PIKfyve/Fab1 is required for efficient V-ATPase and hydrolase delivery to phagosomes, phagosomal killing, and restriction of Legionella infection

Abstract: By engulfing potentially harmful microbes, professional phagocytes are continually at risk from intracellular pathogens. To avoid becoming infected, the host must kill pathogens in the phagosome before they can escape or establish a survival niche. Here, we analyse the role of the phosphoinositide (PI) 5-kinase PIKfyve in phagosome maturation and killing, using the amoeba and model phagocyte Dictyostelium discoideum . PIKfyve plays important but poorly understood roles in vesicular traff… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 40 publications
(61 citation statements)
references
References 107 publications
(135 reference statements)
3
57
1
Order By: Relevance
“…This is often referred to as early maturation and occurs within the first 10 minutes post-engulfment. During this period phagosomes and macropinosomes are marked by the lipid PI(3)P (Buckley et al, 2019;Clarke et al, 2010). Although it has not been confirmed in Dictyostelium, in mammalian cells this is generated by activation of the class III PI-3 kinase by Rab5 (Christoforidis et al, 1999b;Vieira et al, 2001).…”
Section: Early Delivery Eventsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is often referred to as early maturation and occurs within the first 10 minutes post-engulfment. During this period phagosomes and macropinosomes are marked by the lipid PI(3)P (Buckley et al, 2019;Clarke et al, 2010). Although it has not been confirmed in Dictyostelium, in mammalian cells this is generated by activation of the class III PI-3 kinase by Rab5 (Christoforidis et al, 1999b;Vieira et al, 2001).…”
Section: Early Delivery Eventsmentioning
confidence: 99%
“…More recent studies have implicated PIKfyve, a PI-5 kinase, in the efficient delivery of V-ATPase (Buckley et al, 2019). PIKfyve catalyses the conversion of PI(3)P to PI(3,5)P 2 , and knockouts of PIKfyve have slower V-ATPase delivery to early phagosomes, and consequently are defective in acidification (Buckley et al, 2019). PIKfyve is also important for hydrolase delivery and proteolysis (see below).…”
Section: Early Delivery Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wildtype L. pneumophila replicated more efficiently in D. discoideum lacking two or five class I PI3Ks (51,64) or in amoebae lacking PIKfyve (70), a PI 5-kinase, which is recruited through its FYVE domain to early endosomes, where it phosphorylates PtdIns(3)P to yield PtdIns(3,5)P 2 . While it is not clear how lower levels of PtdIns(3,4,5)P 3 promote the intracellular replication of L. pneumophila, the reduction of PtdIns(3,5)P 2 impairs the bactericidal endocytic pathway, which restricts bacterial killing and thus benefits the pathogen (70). The disruption of D. discoideum PTEN (phosphatase and tensin homolog), a PI phosphatase antagonizing PI3Ks, reduces the uptake of L. pneumophila but does not affect intracellular growth (64).…”
Section: Eukaryotic Pi Kinases Implicated In Uptake and Endocytosis Omentioning
confidence: 99%
“…Genetic studies involving knockout mutants, unbiased mutational screens, genome-wide transcriptional changes and proteomic analysis during phagocytosis, macropinocytosis or infection have produced a large wealth of data, which have been the subject of several reviews in the last years (Bozzaro and Eichinger, 2011;Dunn et al, 2018;Cardenal-Muñoz et al, 2018;Swart et al, 2018). Among more recent data not yet covered by reviews, it is worth mentioning: (I) evidence that Dictyostelium cells are highly sensitive to bacterial chemoattractants, but phagocytosis per se is independent of chemoreceptor sensing (Meena and Kimmel, 2017); (II) in apparent contrast to this, the characterization of the G protein-coupled, folic acid receptor fAR1, which recognizes the saccharide core of LPS and stimulates gram-negative bacterial phagocytosis, providing a plausible mechanism for the involvement of G proteins in phagocytosis ; discrepancy between both results may be due to the different phagocytosis assays used; (III) evidence that Dictyostelium discriminates between Gram-(-) and Gram-(+) bacteria, migrating preferentially toward Gram-(-) bacteria (Rashidi and Ostrowski, 2019), and that their growth on Gram-(-) or Gram-(+) bacteria elicit different transcriptomic profiles, with some genes essential for growth (Nasser et al, 2013); ((IV) the identification of PIKFyve/FAB1 in controlling acidification of phagosomes (Buckley et al, 2019), thus extending previous studies on the role of phosphoinositides in phagocytosis, macropinocytosis and resistance to pathogens (Swart et al, 2018;Hoeller et al, 2013;Peracino et al, 2010; (V) Similarly, it has been shown that the RasGAP IqgC is a negative regulator of macropinocytosis and large particle phagocytosis (Marinović et al, 2019), strengthening the role of Ras signalling in these processes Junemann et al, 2016;Bolourani et al, 2010; (VI) While bacterial phagocytosis is essential for growth, it has also been shown that during slug stage, cells maintain as endosymbionts bacteria that have been coated with the secreted lectin discoidin I, and that could possibly be used later as a food source (Dinh et al, 2018).…”
Section: Biological Processmentioning
confidence: 99%